GATA Transcription Factor in Common Bean: A Comprehensive Genome-Wide Functional Characterization, Identification, and Abiotic Stress Response Evaluation - Abdulla, Mohamed Farah; Mostafa, Karam; Aydin, Abdullah; Kavas, Musa; Aksoy, Emre (Springer, 2024)
The GATA transcription factors (TFs) have been extensively studied for its regulatory role in various biological processes in many plant species. The functional and molecular mechanism of GATA TFs in regulating tolerance to abiotic stress has not yet been studied in the common bean. This study analyzed the functional identity of the GATA gene family in the P. vulgaris genome under different abiotic and phytohormonal stress. The GATA gene family was systematically investigated in the P. vulgaris genome, and 31 PvGATA TFs were identified. The study found that 18 out of 31 PvGATA genes had undergone duplication events, emphasizing the role of gene duplication in GATA gene expansion. All the PvGATA genes were classified into four significant subfamilies, with 8, 3, 6, and 13 members in each subfamily (subfamilies I, II, III, and IV), respectively. All PvGATA protein sequences contained a single GATA domain, but subfamily II members had additional domains such as CCT and tify. A total of 799 promoter cis-regulatory elements (CREs) were predicted in the PvGATAs. Additionally, we used qRT-PCR to investigate the expression profiles of five PvGATA genes in the common bean roots under abiotic conditions. The results suggest that PvGATA01/10/25/28 may play crucial roles in regulating plant resistance against salt and drought stress and may be involved in phytohormone-mediated stress signaling pathways. PvGATA28 was selected for overexpression and cloned into N. benthamiana using Agrobacterium-mediated transformation. Transgenic lines were subjected to abiotic stress, and results showed a significant tolerance of transgenic lines to stress conditions compared to wild-type counterparts. The seed germination assay suggested an extended dormancy of transgenic lines compared to wild-type lines. This study provides a comprehensive analysis of the PvGATA gene family, which can serve as a foundation for future research on the function of GATA TFs in abiotic stress tolerance in common bean plants. This study comprehensively explored the GATA transcription factor family in the common bean genome, identifying 31 PvGATA genes and uncovering their role in abiotic stress tolerance. Notably, PvGATA28 demonstrated enhanced stress resistance in transgenic lines, offering promising insights for further research in common bean plant resilience.
Aksoy, Emre/0000-0002-9410-2715; Mostafa, Karam/0000-0003-2286-0434; Kavas, Musa/0000-0001-5903-2873; Aydin, Abdullah/0000-0003-1628-8064; Abdulla, Mohamed Farah/0000-0001-6454-1410;
Keywords: GATA Transcription Factor; Common Bean; Abiotic Stress Response; Functional Characterization; Gibberellic Acid